2008
DOI: 10.1111/j.1469-185x.2008.00045.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological plasticity in scleractinian corals

Abstract: When describing coral shape and form the term phenotypic plasticity, i.e. environment-induced changes in morphology, is often used synonymously with intraspecific variation. Variation, however, may simply be due to genetic differentiation (polymorphism). Of the 1314 extant scleractinian coral species, less than 20 have been tested for plastic responses. Morphological plasticity has important implications for coral identification, as skeletal features used in coral systematics are directly affected by environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
372
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 380 publications
(383 citation statements)
references
References 139 publications
10
372
0
1
Order By: Relevance
“…We suspect that this coral species is highly resilient and therefore dominant in the reefs close to Stone Town. Presumably, corals adjust their skeletal shape to the main constraining environmental factors that control morphological specialization in corals, e.g., light intensity, water movement and sedimentation rates (Todd, 2008). Furthermore, our findings suggest that this mechanism drives beta diversity in our study sites as we found small scale (colony level) differences in the morphological strategies among sites (Figure 3).…”
Section: Discussion Community Compositionsupporting
confidence: 56%
See 2 more Smart Citations
“…We suspect that this coral species is highly resilient and therefore dominant in the reefs close to Stone Town. Presumably, corals adjust their skeletal shape to the main constraining environmental factors that control morphological specialization in corals, e.g., light intensity, water movement and sedimentation rates (Todd, 2008). Furthermore, our findings suggest that this mechanism drives beta diversity in our study sites as we found small scale (colony level) differences in the morphological strategies among sites (Figure 3).…”
Section: Discussion Community Compositionsupporting
confidence: 56%
“…All study sites are protected from swells (Shaghude et al, 2002) and tides have an equal effect on all the study sites. Tidal-induced currents although energetic (5 to 20 cm s −1 ), would not mechanically break corals, in contrast to wave-exposed coral reefs (Todd, 2008).…”
Section: Discussion Community Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…As they are sessile or have restricted capacity for movement (e.g., free-living and/or solitary), corals are subjected to the environmental conditions at their place of settlement. Consequently, they exhibit considerable morphological plasticity, driven in part by various ecological factors (Foster 1979a(Foster , b, 1980Best et al 1984;Hoeksema 1991;Budd 1993;Todd 2008). According to Lowenstein (1985), taxonomic research based exclusively on morphology is plagued by two major limitations.…”
Section: Integrating Molecular and Morphological Evidencementioning
confidence: 99%
“…Moreover, our work 395 suggests that surface area and volume, as well as the ratios between these variables 396 and PL TSA, are potential candidates as useful traits. This shift in focus would also 397 address the fact that corals can exhibit a high degree of morphological plasticity 398 within species (Todd 2008), with colonies of the same species fulfilling different 399 categories of morphotype. This level of plasticity suggests that when our equations 400 are used in the future they should be applied based on the morphotype observed in the 401 field, rather than one that is based on species identification.…”
mentioning
confidence: 99%